Study of the effect of the compound nano-titanium dioxide prepared by Sol-Gel method through two stages on bacteria (E. coli and Streptococcus) as an antimicrobial agent. - Firas. H- Ibrahim; Olfat A. Mahmood (Genius Journals, 2022)
Using titanium tetrachloride (TiCl4) as a starting material and altering the applied temperature in the range of ( 350 ,650nad ,850)℃, titanium dioxide (TiO2) Nano-particles (NPs) are made using the sol-gel method. X-ray diffraction (XRD) and transmission electron microscopy have been used to evaluate the primary characteristics of the produced NPs (TEM). TiO2 nanoparticles were primarily tested for their efficacy as an antibiotic and antibacterial agent using two different bacterial strains (E. coli and Streptococcus). According to XRD results, the titanium dioxide structure exhibits an anatase phase between 350 and 650 °C and a rutile phase at 850 °C. For anatase, the size of the particles is reported to be between (7.17 and 21.4 nm), while for rutile (30.41 nm). According to FTIR analysis, the majority of peaks are seen between 400 and 700 cm-1 as a result of bending and oscillation lengthening. The two phases of TiO2 can use the antibacterial compounds against the two types of bacteria (E. coli and Streptococcus). The obtained results show that antibacterial agents made of TiO2 in the anatase or rutile phases are effective
Keywords: TiO2 Phases; Sol-Gel Process; Precursor; Antibacterial